Computational insights into the magnetoelectronic and half-metallic tendencies of K₂NaXI₆ (X = Sc, Ti, V) double perovskite compounds - Kheir Allah, Mohammed; Bensaid, Djillali; Mokaddem, Khadidja; Bensafa, Imad Khaled; Nour-Eddine Benkhettou; Bencherif, Kaddour (Journal of materials research, 2025)
Double perovskites have gained prominence in materials science due to their unique properties and diverse applications. Our study explores the magnetoelectronic characteristics of the K₂NaXI₆ series, where X is Sc, Ti, or V. We employed density functional theory (DFT) calculations using the PBEsol functional and the KTB-mBJ method to predict magnetic properties accurately. Our results revealed distinct electronic behaviors within the series. K₂NaScI₆ exhibited semiconducting properties with a direct band gap at the Γ point, suggesting potential for light-emitting and absorbing applications. Conversely, K₂NaTiI₆ and K₂NaVI₆ displayed half-metallic behavior with band gaps in the minority spin channel, indicating potential for spin-dependent electronic transport. To further understand chemical bonding and interactions, we conducted Bader charge analysis and electron density calculations. These investigations provide comprehensive insights into the charge distribution and bonding characteristics of these promising double perovskite materials. Graphic abstract